The Humidity Dependence of Pentacene Organic Metal-Oxide- Semiconductor Field Effect Transistor - Fadliondi Fadliondi; Muhammad Kunta Biddinika; Shun-ichiro Ohmi (Universitas Ahmad Dahlan, 2017)
Metal-oxide-semiconductor field-effect transistors (MOSFET) were fabricated using organic semiconductor pentacene. The humidity dependence of drain current gate voltage (ID-VG) characteristic and drain current drain voltage characteristic (ID-VD) will be explained. Firstly, the thermal oxidation method was used to grow SiO2 gate insulator with thickness of 11 nm. Secondly, the thermal evaporation method was used to form Au source and drain electrodes with thickness of 28 nm. The channel width and length of the transistors were 500 mm and 200 mm, respectively. By the same method, organic semiconductor material pentacene was deposited with thickness of 50 nm at vacuum of 7.8x10-6 Torr. The hole mobility decreased from 0.035 cm2/(Vs) to 0.006 cm2/(Vs), while the threshold voltage increased from 0.5 V to 2.5 V and gate leakage current also increased from 5.8x10-10 A to 3.3x10-9 A when the relative humidity increased from 20% to 70%.